Perancangan Sistem Informasi Pengolahan Administrasi Keuangan Pada Dinas P3A-PMD Kabupaten Kepulauan Talaud - Martha Ruth Alotia; Alprita Parasala; Eliyah Acantha M Sampetoding; Inriawati Parauba; Yus Martin Sipota (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
Financial Administration Processing is a process that converts financial data into information, in carrying out this process often using a computer so that it can run automatically. Through a data processing system, it can facilitate organizations to manage financial data for related fields so that they can help complete activities in the financial sector, especially for the process of recording and financial reports quickly. The purpose of this study is to find out how efficient and accurate the information system is at the Office of Women's Empowerment, Child Protection, Community and Village Empowerment in the Talaud Islands Regency (P3A-PMD). The method used in this study is a qualitative method by finding out how efficient and accurate the information system is currently running at the P3A-PMD Office. Data was collected by means of observation, interviews, and literature study. Sources of data used are primary data and secondary data. Data management with a computer is expected to help the process of recording data so that data storage will be better and if an error occurs, you can directly edit the data.